Aplikasi Pembelajaran Kosa Kata Untuk Anak Berkebutuhan Khusus Tunarungu Menggunakan Metode Algoritma Fisher-Yates - Aggry Saputra; Zulfachmi Zulfachmi; Agung Alviandi (LPPM Universitas Putera Batam, 2023)
Deafness is a type of special need that is of concern to the government in terms of equality in obtaining education as stated in Law of the Republic of Indonesia No. 20 of 2003 concerning National Education Chapter IV Article 5 paragraph (1) states that